PELATIHAN DAN PENDAMPINGAN PRODUKSI MIKROORGANISME LOKAL (MOL) UNTUK KEMANDIRIAN PETANI - Jafar, Jusmiati; Ramli, Yuliarti; Kurniawan, Edi (MALLOMO: Journal of Community Service, 2023)
MOL (Local Microorganisms) are commonly cultivated microorganisms. MOL contains Azotobacter sp., Lactobacillus sp., and photosynthetic bacteria function in decomposing organic compounds. MOL is a composting concept that can be completed in 3 weeks. The main raw material in making MOL consists of 3 components, namely: Carbohydrates: rice washing water (starch), used rice (stale) which is often used is starch water. Glucose: from brown sugar, granulated sugar and coconut water and Sources of bacteria: golden snail, gamal leaves, and so on. Just choose materials that are easily available around us. The steps in making MOL: 1. Separating the leaves from the mother petiole, 2) Gamal leaves are crushed using a mortar or in a blender, 3) Mix the mashed Gamal leaves with rice washing water and brown sugar, 4) after all the ingredients put the mixture in a jerry can or airtight container, 5) After about 3 weeks the MOL can be harvested, 6) MOL is considered successful or finished if it gives off an aroma like the smell of tape, 7) Filter the MOL results. For the use of MOL gamal leaves as a pesticide, use a solution of 1 liter of MOL gamal leaves mixed with 5 liters of water. for use as liquid fertilizer, a MOL solution of gamal leaves is used with a ratio of 1: 10 liters of water.